2014
DOI: 10.1016/j.apnu.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Psychiatric Nursing: Examining the Interplay of Autonomy, Leadership Style, and Depressive Symptoms

Abstract: It is important to consider ways in which nurses can be protected from experiencing the effects of burnout. This study examined the relationships between leadership style of psychiatric nurse supervisors, work role autonomy, and psychological distress in relation to psychiatric nurse burnout. Eighty-nine psychiatric nurses from Montana and New York hospitals completed an online survey that assessed their work-related experiences. Overall, results of this study indicate that the participants were experiencing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 31 publications
2
57
0
Order By: Relevance
“…A research conducted with 89 psychiatric nurses from American hospitals revealed high levels of emotional exhaustion among professionals (Madathil, Heck, & Schuldberg, 2014). Similarly, in Brazil it was identified that 25% of professionals (social workers, nursing assistants/technicians, Maringá, v. 38, n. 1, p. 39-47, Jan.-June, 2016 nurses and psychologists) from a psychiatric hospital feel frustrated with their jobs, and 28.1% overloaded (Alves et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A research conducted with 89 psychiatric nurses from American hospitals revealed high levels of emotional exhaustion among professionals (Madathil, Heck, & Schuldberg, 2014). Similarly, in Brazil it was identified that 25% of professionals (social workers, nursing assistants/technicians, Maringá, v. 38, n. 1, p. 39-47, Jan.-June, 2016 nurses and psychologists) from a psychiatric hospital feel frustrated with their jobs, and 28.1% overloaded (Alves et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain the total score of the questionnaire, the scores of all items were summed up and calculated. Reliability of the questionnaire was calculated through Cronbach's alpha in the study of Madathil, Heck, and Schuldberg (2014) (0.7787) [15], and in this study, career independence was calculated as 0.649 in a pilot test. Validity of the questionnaires was approved by the professors of nursing and midwifery faculty.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, those who have little independence also want to have a supportive and friendly leadership style. In supportive leadership style, the leader highly pays attention to the staff and there is friendly communication between the leader and subordinates [11]. Ronie and Gotlib (2007) showed that subordinates with high or low career independence prefer supportive leadership style [10].…”
Section: Introductionmentioning
confidence: 99%
“…Also they argue that the model of Maslach is not suitable for the employees whose working activity is not related to dealing with clients (Kristensen et al, 2005;Madathil, Heck & Schuldberg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that ethical leadership reduces employees' occupational burnout (Madathil, Heck, & Schuldberg, 2014) (2013), ethical manager creates favourable conditions to achieve professional and personal development of the employees. This leads to positive assessment of manager, higher well-being and the sense of happiness.…”
Section: Introductionmentioning
confidence: 99%